Pengantar Editor-in-Chief untuk Volume 12 Nomor 1 Tahun 2026 - Prasetyo, Ridwan Aji Budi (Universitas Brawijaya, 2026)
This editorial introduces the first issue of Volume 12 of Mediapsi, which presents five empirical articles from diverse areas of psychological research in Indonesia. The articles address adolescent mental health and healthy lifestyle behaviours, conflict resolution dynamics in long-term marriages, career-related predictors of university student psychological well-being, the role of organisational support in shaping unpaid interns' work engagement and performance, and the cognitive consequences of time pressure in academic evaluation contexts. Taken together, the contributions reflect a thematic concern with psychological resources and their role in sustaining individual functioning across personal, relational, organisational, and situational domains. The editorial situates each article within this broader framework and highlights key theoretical and practical implications for researchers, educators, counsellors, and organisational practitioners. Editorial ini mengantarkan edisi pertama Volume 12 Mediapsi yang memuat lima artikel empiris dari berbagai bidang kajian psikologi di Indonesia. Kelima artikel membahas kesehatan mental remaja dan perilaku gaya hidup sehat, dinamika resolusi konflik dalam pernikahan jangka panjang, prediktor berbasis karier terhadap kesejahteraan psikologis mahasiswa, peran dukungan organisasi dalam membentuk keterikatan kerja dan kinerja mahasiswa magang tanpa upah, serta konsekuensi kognitif dari tekanan waktu dalam konteks evaluasi akademik. Secara keseluruhan, kelima kontribusi ini mencerminkan perhatian tematik terhadap sumber daya psikologis dan perannya dalam menopang fungsi individu di berbagai domain, baik personal, relasional, organisasional, maupun situasional. Editorial ini menempatkan setiap artikel dalam kerangka tersebut dan menyoroti implikasi teoritis dan praktis yang relevan bagi peneliti, pendidik, konselor, dan praktisi organisasi.